ANALISIS KELAYAKAN USAHA MINYEUK PRET DI DESA LAM ARA KECAMATAN BANDA RAYA KOTA BANDA ACEH - Elly Susanti (Universitas Teuku Umar, 2019)
The purpose of this study is to analyze the level of business feasibility in the market and marketing, technical and technological as well as financial aspects that include investment valuation criteria and sensitivity analysis. The result of feasibility test shows that in the market and marketing aspect, the increasing demand of perfume from previous years as well as good marketing mix strategy can support the feasibility of this business. On the technical and technological aspects it is found that strategic business location, raw materials with good quality, advanced technology, skilled workers in their fields support the feasibility of this business. In the financial aspect, it is found that by using feasibility analysis tool, the value of NPV is Rp. 178.923.542, Net B / C of 2.88, IRR of 51.84%, BEP obtained in the 2nd, 1st and 5th years, and PBP can be returned in the 2nd day of the 2nd day With all the aspects assessed, this business is feasible to run. In the sensitivity analysis with assumption I that is cost 5% increase and fixed benefit, assumption II that is fixed and benefit cost down 5%, assumption III that cost 10% increase and fixed benefit, this business still feasible to run, but at assumption IV that is cost fixed and benefit down 10%, this business is no longer feasible to run because it does not meet the eligibility criteria.